From book to stage to screen: semiotic transformations of Gothic horror genre conventions. Issue 4 (7th August 2016) - Tan, Sabine; Wignell, Peter; O'Halloran, Kay L.
ABSTRACT: This paper adopts a multimodal social semiotic approach for exploring the semiotic changes involved in the transformation of a novel into stage and screen productions. It examines how semiotic resources are deployed in each medium through elements of mise-en-scène, such as speech, music, sound, lighting, props, staging, and cinematographic techniques, and the viewing perspectives that are thus established for audiences. The genre of Gothic horror is selected for this purpose, given how this form of performance has transfixed audiences for centuries and has been adapted for both the stage and the screen. In order to demonstrate how each performance medium has produced its own unique set of foregrounding devices to enthral and captivate audiences, a comparative analysis of excerpts from the novel The Woman in Black by Susan Hill, a videotaped theatrical performance, and the 1989 British television film of the same name is undertaken. The paper discusses the implications of the multimodal semiotic approach for developing a better understanding of the semiotic transformations that horror genre conventions undergo in different media and the viewership positions that are thus re-drawn for audiences. The paper concludes with a view of multimodal recontextualisation processes which form the underlying basis of human sociocultural life.